Calculation of Pneumatic Device for Working Chamber of Saw Gin (Texas Journal of Engineering and Technology, 2023)
In the article is presented a schematic diagram of a pneumatic actuator developed for the mechanism of lifting and lowering the working chamber of a saw gin. The air consumption per one working cycle of the pneumatic device and the system start-up time are determined. The structure of the pneumatic actuator that meets the requirements of the conditions for lifting and lowering the working chamber is selected. The method of controlling the velocity of the rod, the control of its velocity, the location of the output link, the parameters of the air orientation and the control apparatus are determined